Inorganic Phosphorus Transformation and Phosphorus Adsorption–Desorption Properties of Soil in a Cotton Field Under Mulched Drip Irrigation in Xinjiang: A Four-Year Field Assessment - Tang, Xuexia; Liu, Meijuan; Sheng, Jiandong; Chai, Zhongping; Feng, Gu; Chen, Bolang (Frontiers in Environmental Science, 2022)
Phosphorus (P) fertilizer is generally applied to enhance the soil P pool and meet crop demand, but most added P is adsorbed by soil. This study aimed to explore the importance of these P fractions and adsorption–desorption characteristics on the demand for P fertilizer to determine the optimum P fertilizer amount for a cotton field under mulched drip irrigation in Xinjiang, China. A four-year experiment (2016–2019) was conducted in a cotton field to evaluate the effects of five P fertilizer addition levels (0, 75, 150, 300, and 450 kg P2O5 ha−1 year−1) on inorganic P fractions and P adsorption–desorption properties at different soil depths, and explore the effects of soil properties on P adsorption. The four-year continuous P fertilization enhanced inorganic P contents and altered the proportions of the various P forms. A large proportion of the P accumulated in soil was transformed into Ca8-P, followed by Ca2-P, mainly in the surface layer. The accumulation and transformation of P in fertilized soil reduced P adsorption and enhanced P desorption. The soils with higher P application levels had higher inorganic P accumulation with lower adsorption and higher desorption. The total P and Olsen-P in 0–5 cm soil layer; Ca8-P and calcium carbonate (CaCO3) in the 5–10 cm soil layer; Olsen-P, Ca10-P, clay and cation exchange capacity in the 10–20 cm soil layer; and Olsen-P in 20–40 cm soil layer significantly affected the P adsorption–desorption (P < 0.05). The application rate of 75–150 kg P2O5 ha−1 year−1 produced lower inorganic P accumulation, favorable adsorption–desorption properties, and high cotton yield and thus could be considered the optimal P fertilizer application level.